Atividade pesqueira e organização social: o caso das comunidades Igarapé Grande, João Pilatos e Cajueiro - VIANA, Janise Maria Monteiro Rodrigues (Universidade Federal do Pará, 2018)
This study aims to examine how fishing activity is structured and is related to the processes of social organization existing in Amazonian island communities, specifically seeking to understand if social organizations related to fishing activity are developing their social, political and economic role starting from with the associated relationship and society. For this purpose, the communities of Igarapé Grande and João Pilatos were located on João Pilatos Island and the Cajueiro community, located on Santa Rosa Island, an island region of the municipality of Ananindeua (Pa). These communities were selected because they are: considered the oldest, have the largest number of inhabitants and shelter multiple social organizations that work with fishing workers. As far as the organizations in these territories are concerned, the present research is focused on the following: the Association of Rural Igarapé Grande Residents and Small Producers - AMPPRIG, Association of Artisanal Fishermen, Aquaculture, Seafood and Rural Producers of the Ananindeua Islands - APAAPRIAN , Association of Residents and Small Rural Producers of João Pilatos - AMPPRJP and the Fishermen's Colony of the municipality to Z-93, since these institutions are related to the structuring and development of the fishing activity in the municipality. The literature that underlies the research runs through the concepts of community, social organization, associativism, social movements and fishing activity. Studies on the Amazon and the characteristics of artisanal fishing are also debated and studied in depth. A case study of a qualitative nature was carried out, using Narrative Research as a methodological tool. The data and information presented here were collected in the field through semi estructured interviews, observations, documentary analyzes, field notes, photographic and audiovisual records, subsidized by the cited bibliographic review. It is concluded that social organizations constitute a strategic force capable of providing better local living conditions for people, whether in rural areas or in urban centers, enabling greater social participation and closer ties between society and public power, under all their dimensions, and these types of organizations can be inserted as an alternative of local development and social sustainability. However, the organizations object of this study point to the need for structuring and organizational so that they can benefit not only the associated fishermen, but also contribute to the strengthening of the category through support with the Colony. The results presented make possible repercussions both in the theoretical field and in the practical field, since the surveys related to social organizations and fishing activity in the municipality of Ananindeua are scarce, and these studies may eventually contribute to the objectives and actions of these social representations.